Debating governance - Pierre,Jon(ed.) (New York, 2006)
Leading scholars in the field of governance examine the effectiveness of the different non-institutional strategies at the disposal of modern governments in tackling issues of urban decline, public administrations, governmental regionalization, budget deficits, and global economics.
Keywords: Governance